Pengembangan Sistem Deteksi Kualitas Minyak Goreng Sawit Berbasis Fuzzy Logic - Ariyanto, Adhitiya Dwijaya; Hariadi, Balok; Swarga, Lutfi Agung; Santoso, Santoso; Hartayu, Ratna (Institut Teknologi Adhi Tama Surabaya, 2025)
ABSTRACT Palm cooking oil is a widely used staple, but its quality deteriorates with repeated use, posing health risks. Traditional methods for assessing oil quality remain subjective, necessitating a more objective detection system. This study develops a fuzzy logic-based palm cooking oil quality detection system using a color sensor (TCS3200), clarity sensor (SEN0189), and odor sensor (TGS2600) controlled by Arduino UNO. The system classifies oil into three categories: Safe to Use, Moderately Safe, and Not Safe. Testing results indicate a classification accuracy of 90%, with a confidence level of 95% for safe oil and 88% for unsafe oil. This system provides a practical, objective, and efficient solution for evaluating cooking oil quality, making it applicable for improving food safety in both households and industries. Keywords: Fuzzy logic, palm cooking oil, color sensor, clarity, odor, Arduino.